Geostatistical techniques applied to spatial distribution of macroorganisms in soybean crop - Lovera, Lenon Henrique; Lima, Elizeu De Souza; Montanari, Rafael [UNESP]; de Souza, Zigomar Menezes; Farhate, Camila Viana Vieira; Campos, Milton Cesar Costa; Torres, José Luiz Rodrigues (Southern Cross Publishing, 2018)
The use of geostatistical techniques has allowed the monitoring of macrofauna spatial variability in crops of economic interest, enabling the creation of maps and more adequate management strategies. The aim of this study is to analyze the spatial dependence of the macrofauna and correlate it to the soybean crop yield along an agricultural year regarding a Hapludox loamy soil with an even slope of 0.025 m m-1. The determination of the sampling points of the macrofauna as well as the soybean yield was carried out through a geostatistical mesh. During the soybean growth, we carried out four applications of insecticides for pest control. In the end of the cycle, the soybean grain yield was determined in an area of 3.24 m2 located around the sampling point. Macrofauna collecting was carried out by using a solution of acetylsalicylic acid diluted in water inside a plastic container. The analysis of the spatial dependence was performed by calculating its semivariogram, based on the stationarity assumptions of the intrinsic hypothesis. Organisms in the taxonomic group Hymenoptera (groups of insects that comprise wasps, bees and ants) were the most frequent at the experimental area. Only soy grain yield and the Coleoptera class presented spatial dependence (when the associated variable resembles more the value of the samples in the vicinity than the rest of the locations of the sample set). Coleoptera showed higher spatial concentration in regions of highest soybean yields.
Keywords: Grains yield; Insects; Pests; Spatial variability; Statistical techniques